A Critical Cross-Species Comparison of Pollen from Nelumbo nucifera Gaertn. vs. Nymphaea lotus L. for Authentication of Thai Medicinal Herbal Tea - Duangjai Tungmunnithum; Sullivan Renouard; Samantha Drouet; Jean-Philippe Blondeau; Christophe Hano (Plants, 2020)
“Bau Luang” or Nelumbo nucifera Gaertn. is an aquatic medicinal herb that has been used as a component of traditional medicines, medicinal products, and herbal tea for good health, particularly in Asia. The stamen of N. nucifera is an important part of this medicinal plant that is used in the form of dried and/or powdered stamens for herbal tea as well as the main ingredient of some traditional remedies. However, there is another aquatic herb called “Bau Sai” or Nymphaea lotus L. that is distributed in similar locations. Living plants of these two aquatic species may be classified according to their morphology, but the dried and powdered stamens of these two medicinal species are difficult to distinguish. The major reason of adulteration is the higher price of Bau Luang stamen. As a result, various methods of authentication, such as pollen micromorphology evaluation using scanning electron microscopy (SEM) analysis, bioinformatics analysis of two nuclear and plastic DNA markers, phytochemical stamen profiling, and Fourier transform infrared (FTIR) analysis of stamen plant material authentication from Bau Luang and Bau Sai, have been used in this present research in order to avoid some adulteration and/or misuse between the dried stamens of Bau Luang and Bau Sai. These results showed that the micro-morphology of pollen (size of pollen grain, number of apertures, and surface ornamentation) from the SEM analysis, some phytochemical compounds and the FTIR sporopollenin-to-protein ratio signal analysis are potential tools for authentication and identification of these two medicinal plants from their dried-stamen materials. This model of investigation may also be used to distinguish dried plant material from other problematic plant groups.